Między przekładem, komentarzem a interpretacją — uwagi na marginesie anglojęzycznego podręcznika literatury polskiej - Skwara, Marta (Przekłady Literatur Słowiańskich, 2018)
In-between Translation, Commentary and Interpretation — Remarks on the Margins of an English Language History of Polish Literature The paper is devoted to the reciprocal connections among three “metatexts”: translation, commentary, and interpretation. On the basis of Antoine Berman’s theoretical assumptions I demonstrate how these three “reformulations” are intertwined in order to analyze chosen pieces of Polish poetry in English translation. My aim is to explore various roles which translation, commentary and interpretation can play in presenting Polish literature to foreign readers. KEY WORDS: translation, commentary, interpretation, intertextuality, Polish literature